Predicting mobile learning culture model among students of Higher learning institutions: implications on curriculum design - Hashim, Che Noraini; Syed Hassan, Sharifah Sariah; Mohammed Rawash, Fouad Mahmoud; Abdullah, Norillah (UPM Press, 2017)
The advancement in computer and communication technologies has enriched the communication and learning methods, demanding for further improvement in the curriculum design. This study explores the mobile-learning (m-learning) culture among students of the Malaysian institutions of higher learning (IHL). Two objectives had been set: Firstly to establish a culture of mobile wireless technology (MWT) application in learning at tertiary level of education; and to design a curriculum and validate the m-learning model incorporating the learning culture at higher learning institutions involving components such as ethics, social norms and attitude. A survey was carried out on 490 random samples drawn from five universities and one community college students, in Malaysia. Data collected were analysed using descriptive statistics to address the first objective of the study. A Structural Equation Model (SEM) of mobile learning culture at the institute of higher learning (IHL) had been designed and validated to fulfil the second objective. The findings suggest that: The Model is able to explain significant contributions from all predictors on the actual use of MWT in learning. In conclusion, the study asserts to the fact that educators should include ethics and behavioral components while designing curriculum for the institution of higher learning in Malaysia.